2019
DOI: 10.1155/2019/4139208
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Behavior of Carbon Fiber-Reinforced Polymer Composites Incorporating Nanomaterials after Exposure to Elevated Temperature

Abstract: This study experimentally examined the effect of nanomaterial on the tensile behavior of carbon fiber-reinforced polymer (CFRP) composites. Multiwalled carbon nanotubes (MWCNT), graphene nanoplatelets (GnPs), and short multiwalled carbon nanotubes functionalized COOH (S-MWCNT-COOH) with 1% by weight were used as the primary test parameters. In the present test, S-MWCNT-COOH was more effective than the others in improving the maximum tensile strength, ultimate strain, and toughness of the CFRP composites. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
2
21
0
1
Order By: Relevance
“…5b). Truong et al [54] also reported similar behaviour, namely adding GNPs did not affect the tensile strength of the CFRP composites, as the dominant load-bearing component during the tensile procedure is the carbon fibres themselves [22]. However, composites with 1.05 vol% GNPs performed nonlinearly when the tensile strain increased up to 0.8%, i.e.…”
Section: Tensile Propertiesmentioning
confidence: 75%
“…5b). Truong et al [54] also reported similar behaviour, namely adding GNPs did not affect the tensile strength of the CFRP composites, as the dominant load-bearing component during the tensile procedure is the carbon fibres themselves [22]. However, composites with 1.05 vol% GNPs performed nonlinearly when the tensile strain increased up to 0.8%, i.e.…”
Section: Tensile Propertiesmentioning
confidence: 75%
“…The stoichiometric ratio between the epoxy resin and hardener was 100:55 by weight. More details of the epoxy resin and hardener were presented in the study by Truong et al [37]. Three types of nanomaterials, namely, MWCNTs, GnPs, and S-MWCNT-COOH, were used as nanofillers.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Both the epoxy resin and hardener had low viscosities ranging from 800 to 1600 cps and from 500 to 1000 cps, respectively, at 25 • C. The stoichiometric ratio between the epoxy resin and hardener was 100:55 by weight. More details of the epoxy resin and hardener were presented in the study by Truong et al [37].…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, GF-PP had the lowest GF content in comparison to CPW-PP and GF-CPW-PP. Previous studies reported that [30][31][32][33] composite failure mechanisms may be represented as follows: when there is no load disruption by the reinforcement break under mechanical testing, the load is uniformly distributed among the fibres next to the break fibre resulting in a degree of concentrated stress developing on those fibres and damaging the surrounding matrix. Therefore, the presence of intense moisture increased vulnerability and decreased the tensile strength of the composites.…”
Section: Morphologymentioning
confidence: 99%